Role of Ferroptosis in Fibrotic Diseases - Zhou J; Tan Y; Wang R; Li X (Dove Medical Press, 2022)
Jian Zhou, Yuan Tan, Rurong Wang, Xuehan Li Department of Anesthesiology, Laboratory of Anesthesia and Critical Care Medicine, West China Hospital, Sichuan University, Chengdu, Sichuan Province, People's Republic of ChinaCorrespondence: Xuehan Li, Department of Anesthesiology, Laboratory of Anesthesia and Critical Care Medicine, West China Hospital, Sichuan University, No. 37 Guoxue Xiang, Chengdu, Sichuan Province, 610041, People's Republic of China, Tel +86 18980099133, Email xuehanli@scu.edu.cnAbstract: Ferroptosis is a unique and pervasive form of regulated cell death driven by iron-dependent phospholipid peroxidation. It results from disturbed cellular metabolism and imbalanced redox homeostasis and is regulated by various cellular metabolic pathways. Recent preclinical studies have revealed that ferroptosis may be an attractive therapeutic target in fibrotic diseases, such as liver fibrosis, pulmonary fibrosis, kidney fibrosis, and myocardial fibrosis. This review summarizes the latest knowledge on the regulatory mechanism of ferroptosis and its roles in fibrotic diseases. These updates may provide a novel perspective for the treatment of fibrotic diseases as well as future research.Keywords: ferroptosis, liver fibrosis, kidney fibrosis, myocardial fibrosis, pulmonary fibrosis